Cost-effectiveness of a Contact Intervention and a Psychotherapeutic Program for Post-discharge Suicide Prevention. (August 2021) - Martínez-Alés, Gonzalo; Cruz Rodríguez, José B.; Lázaro, Pablo; Domingo-Relloso, Arce; Barrigón, María Luisa; Angora, Ricardo; Rodríguez-Vega, Beatriz; Jiménez-Sola, Eduardo; Sánchez-Castro, Pilar; Román-Mazuecos, Eva; Villoria, Lucía; Ortega, Ana José; et al.
Objective: To determine the cost-effectiveness of 2 strategies for post-discharge suicide prevention, an Enhanced Contact intervention based on repeated in-person and telephone contacts, and an individual 2-month long problem-solving Psychotherapy program, in comparison to facilitated access to outpatient care following a suicide attempt. Methods: We conducted a cost-effectiveness analysis based on a decision tree between January and December 2019. Comparative effectiveness estimates were obtained from an observational study conducted between 2013 and 2017 in Madrid, Spain. Electronic health care records documented resource use (including extra-hospital emergency care, mortality, inpatient admission, and disability leave). Direct cost data were derived from Madrid's official list of public health care prices. Indirect cost data were derived from Spain's National Institute of Statistics. Results: Both augmentation strategies were more cost-effective than a single priority outpatient appointment considering reasonable thresholds of willingness to pay. Under the base-case scenario, Enhanced Contact and Psychotherapy incurred, respectively, €2, 340 and 6, 260 per averted attempt, compared to a single priority appointment. Deterministic and probabilistic sensitivity analyses showed both augmentation strategies to remain cost-effective under several scenarios. Enhanced Contact was slightly cost minimizing in comparison to Psychotherapy (base-case scenario: €−196 per averted attempt). Conclusions: Two post-discharge suicide prevention strategies based on Enhanced Contact and Psychotherapy were cost-effective in comparison to a single priority appointment. Increasing contacts between suicide attempters and mental health-care providers was slightly cost minimizing compared to psychotherapy.